Interplay Between Fatty Acids, Stearoyl-Co-A Desaturase, Mechanistic Target of Rapamycin, and Yes-Associated Protein/Transcriptional Coactivator With PDZ-Binding Motif in Promoting Hepatocellular Carcinoma - Jihane N. Benhammou; Jim Sinnett-Smith; Joseph R. Pisegna; Enrique J. Rozengurt (Gastro Hep Advances, 2023)
Nonalcoholic fatty liver disease has reached pandemic proportions with one of its most consequential complications being hepatocellular carcinoma (HCC). Nonalcoholic fatty liver disease-related HCC is becoming the leading indication for liver transplantation in the United States. Given the scarcity of available organs, early detection and prevention remain key in prevention and management of the disease. Over the years, the yes-associated protein (YAP)/transcriptional coactivator with PDZ-binding motif (TAZ) pathway emerged as a key signal transduction pathway in the pathogenesis of HCC. In this review, we explore the interplay between the YAP/TAZ pathway as a point of convergence in HCC pathogenesis. We review the evidence of how lipid reprogramming and key lipid pathways, saturated and monounsaturated fatty acids (through the rate-limiting enzyme stearoyl Co-A desaturase), the mevalonic acid pathway (the role of statins), and mechanistic target of rapamycin all play critical roles in intricate and complex networks that tightly regulate the YAP/TAZ pro-oncogenic pathway.